Aspects of protection of accounting data in the conditions of use of innovation and information technologies - Марценюк, Василь Петрович; Сверстюк, Aндрій Степанович; Андрущак, Ігор Євгенович; Чудовець, Віталій Васильович; Кошелюк, Віктор Андрійович (Луцьк: ЛНТУ, 2021)
The article examines the current state of cybersecurity and identification of cyber threats in the use of credentials, the formulation of measures to minimize the risk of theft, damage or loss of confidential accounting information in the cyber environment of its use and maintenance.
Keywords: cybersecurity; cyberenvironment; protection of accounting information; cyberthreat; cybersecurity.